2020
DOI: 10.1002/pbc.28852
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of dinutuximab therapy for treatment of high‐risk neuroblastoma in two patients with end‐stage renal disease on dialysis

Abstract: Autologous hematopoietic cell transplant (aHCT) has a significant survival advantage in patients with high-risk (HR) neuroblastoma. Transplant-associated thrombotic microangiopathy (TA-TMA) is a serious complication and may result in chronic renal disease leading to delay in subsequent posttransplant therapy and limitations of treatment options. Dinutuximab represents an important therapeutic advance in the treatment of pediatric HR neuroblastoma, but historically has not been administered in patients with GFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although there is a lack of clear recommended time for adjuvant chemotherapy after NB surgery, many studies have suggested that postoperative adjuvant chemotherapy should be carried out as early as possible [ 24 , 25 ]. Emberesh [ 26 ] reported that there was a delay of systematic treatment (including chemotherapy, radiotherapy and immunotherapy) in 2 children with high-risk NB. Even if they subsequently received targeted immunotherapy, they did not escape the recurrence and progression of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a lack of clear recommended time for adjuvant chemotherapy after NB surgery, many studies have suggested that postoperative adjuvant chemotherapy should be carried out as early as possible [ 24 , 25 ]. Emberesh [ 26 ] reported that there was a delay of systematic treatment (including chemotherapy, radiotherapy and immunotherapy) in 2 children with high-risk NB. Even if they subsequently received targeted immunotherapy, they did not escape the recurrence and progression of tumor.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 Second, although GD2 is an ideal target for NB therapy because it is highly expressed on NB tumor cells, it also exists in other normal tissues. 20 , 21 Therefore, dinutuximab stimulates normal GD2 + cells, causing severe pain, fever, low platelet count, infusion reactions, hypotension, elevated liver enzymes, anemia, diarrhea, hypokalemia, capillary-leak syndrome, neutropenia, and lymphopenia. Dinutuximab treatment may result in nerve damage, infections, eye problems, electrolyte abnormalities, and bone marrow suppression.…”
Section: Introductionmentioning
confidence: 99%